Microclimate in agrosilvopastoral system enhances powdery mildew severity compared to agropastoral and non-integrated crop - Roese, Alexandre Dinnys; Ribeiro, Paulo Justiniano; De Mio, Louise Larissa May (Tropical plant pathology, 2017)
While integrated crop-livestock systems including trees have received more attention during the last two decades, the epidemiology of plant diseases in these production systems is still poorly understood. Microclimatic modifications due to the type of cropping system adopted may affect the epidemic patterns. This work aimed to evaluate whether powdery mildew severity on oats ( Avena strigosa and A. sativa ) and on soybean ( Glycine max ) are affected by the cropping system and which microclimatic factors are associated with disease development. A long-term experiment was conducted to compare three systems: agropastoral (AP), agrosilvopastoral (ASP) and non-integrated crop (CO). Two rates of nitrogen (N) were applied for AP and ASP. Powdery mildew severity on oats in ASP was approximately 20× greater than in the others systems. On soybean, powdery mildew varied across systems but it was more severe in ASP, with at least 4× greater disease severity than in the other systems. Likewise, conidia of Microsphaera diffusa collected in spore traps in ASP were consistently higher than in the others systems. ASP showed shorter leaf wetness duration, higher daylight relative humidity (RH), and lower temperature amplitude compared with the other systems. Multiple regression analysis showed that leaf wetness duration and daylight RH explained best the disease variation on soybean. Our data suggest that microclimatic conditions in the ASP system are likely the main drivers of more severe powdery mildew epidemics.